(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
COVID-19 is wreaking havoc on the planet we reside in, with hung markets and citizens confined to their homes in nearly every region of the globe. This pandemic isn’t going anywhere just wreaking havoc on health-care services and people’s lives it’s also wreaking havoc on global markets, culminating in work cuts, business disruptions, and ushering in one of the most despicable periods in human history. About all markets are seeing major market losses, and the effect of this pandemic is so massive that they are expecting far tougher times ahead. This paper examines the many markets that are the ones that are most affected by the pandemic, as well as how this affects employment shortages and the global economy.